Influence of Iron, Folic, Acid, Glucose and Physical Exercise on the Increase of Hemoglobin Level - Raymond IVano A, (Kepelatihan Olahraga, 2010)
This study was aimed to investigate the influence of Iron, Folic Acid, and Glucose and Physical Exercise on the increase of Hb level.Hb level measurement was done twice, before and after intervention used Cyanmethemoglobin method. Based on the results of Anova test, Hb level before intervention in groups 1, 2, and 3 showed no significant difference (p=0.926) with means was 11.985±0,697 g/dl. Means of Hb level before intervention in group I was 12.043+0.674 g/dl, (2) means of Hb level in group II was 11.971+0.698 g/dl, and (3) means of Hb level in group III was 11.943+0.707 g/dl. Results of Anova tests above indicated that Hb level before intervention in groups 1, 2, and 3 had same values. Two months after intervention, the results showed that all groups had significant increase (p=0.000) with means 13,933±0,842 g/dl. Means of Hb level in group I after intervention was 14.850±0.199 g/dl, an increase of 2,807±0,475 gr/dl; means of Hb level in group II was 13.443+0.651, increased 1,472±0,047 gr/dl and (3) means of Hb level in group III was 13.507 + 0.644, an increase of 1,564±0,063 gr/dl. Results of this study showed that (1) The administration of Iron, Folic Acid, Glucose and Physical Exercise increased more than Hb level ; (2) The administration of Iron, Folic Acid, Glucose without Physical Exercise increased Hb level, (3) the administration of Placebo and Physical Exercise also increased Hb level (p=0,000). The increase of Hb level significantly (p=0.001) on the influence of Iron, Folic Acid, Glucose in Physical Exercise, as indicated by Simple Linear Regression Test, in which B = 0,998996; R2 = 0,77246; and T = 3,433. This study can be concluded that on the influence administration of Iron, Folic Acid, Glucose and Physical Exercise increased Hb level (p=0,000).